(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Background & Purpose Asthma is one of the most common chronic diseases in children, with airway inflammation and repeated respiratory symptoms, and it can greatly compromise the quality of life (QoL). It is crucial to understand how asthma affects children’s QoL to enhance the management strategies in primary health care. The objective of this research was to evaluate the QoL in asthmatic children in a primary health care unit and determine factors related to their health status. Methods A cross-sectional study was conducted involving 72 children aged between 4 to 15 years who were diagnosed with asthma. Our study enrolled all clinical outcomes of treatments used, including (short-acting beta agonists, nebulizers, interleukin modifiers, and leukotriene modifiers). Also, this study were assessed throughout the SF-36 QoL Questionnaire, which was employed to evaluate the impact of asthma on physical and mental health.